Godly women : fundamentalism and female power - Brasher, Brenda E., 1952- (Rutgers University Press, 1998)
"Fundamentalist women are often depicted as dedicated to furthering the goals and ideas of fundamentalist men and thus of ancillary importance to the movement as a whole. Godly Women, Brenda Brasher's ethnographic study, reveals the paradox that fundamentalist women can be powerful people in a religious cosmos generally understood to be organized around their disempowerment."--Jacket